Development of the Second Ingredient of the New Product “Yogrik” - Balayan, E. B.; Araksyants, A. E. (ՀԱԱՀ հիմնադրամ)
Research in this area aims to develop a milk-protein product similar to ricotta cheese. This product will be the second component of the newly developed twocomponent Yogrik product, a mixture of yogurt and ricotta. Combination of the biological value of yogurt and ricotta will create a balanced amino acid food. Cheeses obtained by acid and thermo-acid coagulation are usually fresh soft cheese varieties made by the coagulation of milk, cream, whey, or their mixtures, by direct chemical acidification, bacterial cultures coagulation, or by a combination of chemical acidification and high-temperature processing. In appearance and production technology, ricotta is between cheese and cottage cheese. But in terms of the softness of the clot and versatility, it is an outstanding product. Ricotta is rich in proteins including albumin and contains about 11 % protein. Whey cheese proteins are in the most easily assimilated state. Combining the biological value of yogurt and ricotta will create a balanced food with amino acid content.
Keywords: Food Science and Technology